2004
DOI: 10.1007/s10350-003-0049-y
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Dysplasia in Patients With Inflammatory Bowel Disease: A National Survey of Colonoscopic Practice in New Zealand

Abstract: Many New Zealand colonoscopists have a poor understanding of the definition and importance of dysplasia associated with colitis. Although colectomy referral rates are higher in this study than in similar studies, low-grade dysplasia is often not referred for colectomy. Improved education may improve surveillance practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 38 publications
4
41
3
Order By: Relevance
“…Our finding was consistent with prior studies of varied compliance with practice guidelines, in particular the low use of surveillance colonoscopy (25%) for patients with longstanding UC in an integrated healthcare delivery system in the USA [18,19,20,21,22]. IBD patients in our study sample presumably had CRC associated with longstanding colitis, although the retrospective nature of our study precluded detailed information on the duration, extent and severity of colitis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our finding was consistent with prior studies of varied compliance with practice guidelines, in particular the low use of surveillance colonoscopy (25%) for patients with longstanding UC in an integrated healthcare delivery system in the USA [18,19,20,21,22]. IBD patients in our study sample presumably had CRC associated with longstanding colitis, although the retrospective nature of our study precluded detailed information on the duration, extent and severity of colitis.…”
Section: Discussionsupporting
confidence: 81%
“…Adherence to surveillance colonoscopy guidelines for patients with ulcerative colitis (UC) has varied in clinical practice. Surveys of gastroenterologists showed that most gastroenterologists performed some form of surveillance for UC patients [18,19,20]. However, one survey suggested that only about half of IBD specialists and community gastroenterologists would recommend surveillance colonoscopy for a hypothetical patient with left-sided colitis [21].…”
Section: Introductionmentioning
confidence: 99%
“…This number of biopsies was estimated to be necessary to detect possible dysplasia with a sensitivity of 90% [10] . A similar questionnaire-based study in New Zealand showed a median number of 17 biopsies [12] . This again, will inevitably lead to a pronounced decrease in sensitivity, rendering the surveillance tool ineffective.…”
Section: Discussionmentioning
confidence: 75%
“…Even the presence of LGD, which is associated with CRC in 21.4%-54%, can be considered an indication for surgery [4,6] . There is a disconcertingly low referral rate for colectomy amongst Dutch GEs, and even more so when findings are compared with 3 similar questionnaire-based studies in New Zealand, United Kingdom and Canada [12][13][14] . It is remarkable that the referral rate is higher for LGD and much lower for HGD and DALM compared with the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study of both colorectal surgeons and gastroenterologists from New Zealand similarly found poor knowledge of the definition of dysplasia, with only 20% responding correctly. In this group, the colorectal surgeons defined dysplasia correctly more often and understood the significance of low grade dysplasia as well (Geary et al, 2004). Despite clear recommendations from the American Gastroenterological Association to perform four quadrant biopsies every ten cm for a total of thirty to forty biopsies, only 41% of gastroenterologists followed this recommendation.…”
Section: Hurdles To Successful Screening Surveillance Programmentioning
confidence: 99%